Photocatalytic material, preparation method and application thereof, and method for producing hydrogen through photocatalytic ammonia decomposition

By introducing phosphorus and precious metal doping and non-precious metal comodification into the carbon nitride-based photocatalytic material, a photocatalytic material with a covalent skeleton of carbon nitride is formed, and the problems of low efficiency and poor stability of ammonia decomposition and hydrogen production in the prior art are solved, and an efficient and stable ammonia decomposition and hydrogen production effect is achieved, and an environmentally friendly synthesis method is adopted.

CN119702035AActive Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311279384.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

In the prior art, carbon nitride-based photocatalytic materials have low efficiency and poor stability in the process of ammonia decomposition and hydrogen production, and conventional synthesis methods have problems of environmental pollution and health damage.

Method used

Carbon nitride is comodified by phosphorus and precious metals and non-precious metals to form a photocatalytic material with a covalent skeleton of carbon nitride, improving its activity and stability in the hydrogen production of ammonia decomposition.

Benefits of technology

The efficiency and stability of photocatalytic ammonia decomposition and hydrogen production are significantly improved, and the serious problem of single semiconductor carrier recombination of carbon nitride is overcome. The preparation method is simple and easy to control, environmentally friendly and pollution-free.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119702035A_ABST
    Figure CN119702035A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photocatalysis, and discloses a photocatalytic material, preparation and application thereof, and a method for producing hydrogen through photocatalytic ammonia decomposition. The invention relates to a photocatalytic material, the photocatalytic material comprises nitrogen, carbon, phosphorus, a non-noble metal and a noble metal, the photocatalytic material has a carbon nitride covalent skeleton, the phosphorus and the noble metal exist in the carbon nitride covalent skeleton in a doped form, and the non-noble metal is loaded outside the carbon nitride covalent skeleton in an oxide form; the non-noble metal is selected from at least one of iron, cobalt and nickel, and the noble metal is selected from at least one of ruthenium, platinum and palladium. The photocatalytic material contains phosphorus and noble metal doped and non-noble metal co-modified carbon nitride, so that the activity and stability of photocatalytic ammonia decomposition hydrogen production can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalysis, and in particular to a photocatalytic material and its preparation and application, and a method for producing hydrogen by photocatalytic decomposition of ammonia. Background Art

[0002] The development of ammonia as a hydrogen storage medium can connect renewable energy, hydrogen energy and traditional industries, and develop a full-chain "ammonia-hydrogen" green circular economy route that conforms to the characteristics of my country's energy structure, namely "clean and efficient ammonia synthesis → safe and low-cost storage and transportation of ammonia → carbon-free and efficient 'ammonia-hydrogen' utilization", which is of great significance to ensuring national energy and environmental security and sustainable social and economic development. In addition, the development of ammonia as a clean and efficient new energy source not only realizes energy conservation and emission reduction in the traditional synthetic ammonia industry, but also connects renewable energy and new energy industries, and will also have great application prospects.

[0003] Ammonia decomposition is an endothermic reaction. In conventional systems, the reaction temperature usually needs to be above 500-800°C, which consumes a lot of energy and is highly dangerous. Therefore, it is urgent to develop and utilize catalytic materials for ammonia decomposition driven by renewable energy. Photocatalytic technology using semiconductor materials can directly capture solar energy to drive high-value-added chemicals. Research teams from Rice University, Syzygy Plasmonics Inc. and Princeton University in the United States used only cheap and abundant non-precious metals (copper and iron) to create a light-driven catalyst that can operate at room temperature. It only needs the energy of light to convert ammonia into cleanly burned hydrogen. Among the common semiconductor photocatalysts, carbon nitride has a stable structure, excellent physical and chemical properties, and a good spectral response range. It has important applications in photocatalytic water decomposition, pollutant degradation, and ammonia decomposition to produce hydrogen. However, carbon nitride itself is photogenerated, which limits its efficiency. In addition, conventional synthesis methods have certain defects and cannot obtain non-precious metal and phosphorus co-modified carbon nitride materials with high comprehensive performance.

[0004] Chinese patent application CN106492870A discloses a metal oxide doped photocatalyst, the photocatalyst is composed of a metal oxide and a non-metal oxide carbon nitride composite, the metal oxide is selected from at least one of yttrium oxide, zirconium oxide, niobium oxide, molybdenum oxide, technetium oxide, ruthenium oxide, rhodium oxide, palladium oxide, silver oxide and cadmium oxide; its preparation method comprises: step 1: dispersing a compound containing a non-metal element in a first dispersant, adding a nitrogen-containing organic matter to the system, removing the first dispersant after mixing evenly, and then calcining to obtain a non-metal element doped graphite phase carbon nitride; step 2: mixing the non-metal element doped graphite phase carbon nitride obtained in step 1 with a metal oxide, adding a second dispersant organic solvent to disperse, removing the second dispersant after mixing evenly, and then calcining at high temperature, wherein step 1 is carried out in a liquid phase system, and step 2 is carried out in an organic solvent such as ethanol, and it is used for the degradation of azo dyes. However, organic solvents need to be used in the synthesis process, which is easy to cause environmental pollution or health damage, and is not conducive to large-scale production. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems existing in the prior art and provide a photocatalytic material and its preparation and application, and a method for photocatalytic ammonia decomposition to produce hydrogen. The photocatalytic material contains carbon nitride doped with phosphorus and precious metals and co-modified with non-precious metals, which can improve the activity and stability of photocatalytic ammonia decomposition to produce hydrogen.

[0006] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a photocatalytic material, wherein the photocatalytic material includes nitrogen, carbon, phosphorus, non-precious metals and precious metals, the photocatalytic material has a carbon nitride covalent skeleton, phosphorus and precious metals are present in the carbon nitride covalent skeleton in the form of doping, and the non-precious metals are loaded outside the carbon nitride covalent skeleton in the form of oxides; the non-precious metal is selected from at least one of iron, cobalt and nickel, and the precious metal is selected from at least one of ruthenium, platinum and palladium.

[0007] A second aspect of the present invention provides a method for preparing a photocatalytic material, wherein the method comprises the following steps:

[0008] (1) mixing a nitrogen-containing organic compound with a phosphorus source and a noble metal source, and then performing rotary evaporation drying, a first roasting and freeze drying, wherein the noble metal is selected from at least one of ruthenium, platinum and palladium;

[0009] (2) mixing the product obtained in step (1) with a non-precious metal source in the presence of a solvent, wherein the non-precious metal is at least one of iron, cobalt and nickel;

[0010] (3) Under a protective atmosphere, the product obtained in step (2) is subjected to a second calcination, wherein the second calcination comprises first keeping the temperature at 100-200° C. for 0.5-2 h, and then heating the temperature to 210-350° C. for 1-2 h.

[0011] The third aspect of the present invention provides a photocatalytic material prepared by the preparation method described in the second aspect.

[0012] A fourth aspect of the present invention provides an application of the photocatalytic material described in the first aspect or the third aspect in a photocatalytic ammonia decomposition hydrogen production reaction.

[0013] The fifth aspect of the present invention provides a method for producing hydrogen by photocatalytic decomposition of ammonia, wherein the method comprises: in the presence of a photocatalytic material and visible light, a decomposition reaction of the reaction raw material ammonia occurs, and the photocatalytic material is the photocatalytic material described in the first aspect or the third aspect.

[0014] The photocatalytic material provided by the present invention utilizes phosphorus and noble metal doping and non-noble metal co-modification of carbon nitride to increase the carrier density of the semiconductor itself, and simultaneously utilizes the doping energy level to regulate the light absorption performance, thereby overcoming the serious carrier recombination problem of the single carbon nitride semiconductor itself, and greatly improving the activity and stability of photocatalytic ammonia decomposition to produce hydrogen.

[0015] The photocatalytic material provided by the present invention increases the number of surface active sites by in-situ introduction of phosphorus-doped, non-precious metal and precious metal-modified carbon nitride, so that the catalytic material exhibits excellent performance of ammonia decomposition to produce hydrogen, and can further improve the conversion efficiency.

[0016] The preparation method provided by the present invention comprises doping phosphorus and noble metal elements into a carbon nitride precursor to obtain phosphorus- and noble metal-containing carbon nitride, and then realizing co-doping of non-noble metals through in-situ synthesis, so that phosphorus and noble metals exist in the carbon nitride covalent skeleton in the form of doping, and the non-noble metals are loaded outside the carbon nitride covalent skeleton. The preparation method is simple and easy to control, and the carbon nitride structure is complete. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the X-ray diffraction pattern (XRD) of the photocatalytic material of Example 1.

[0018] Figure 2 This is a high-resolution transmission electron microscopy image of the photocatalytic material of Example 1. DETAILED DESCRIPTION

[0019] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0020] A first aspect of the present invention provides a photocatalytic material, wherein the photocatalytic material includes nitrogen, carbon, phosphorus, non-precious metals and precious metals, the photocatalytic material has a carbon nitride covalent skeleton, phosphorus and precious metals are present in the carbon nitride covalent skeleton in the form of doping, and the non-precious metals are loaded outside the carbon nitride covalent skeleton in the form of oxides; the non-precious metal is selected from at least one of iron, cobalt and nickel, and the precious metal is selected from at least one of ruthenium, platinum and palladium.

[0021] In the present invention, through the synergistic modification of the carbon nitride skeleton by phosphorus, non-precious metal elements and precious metal elements, the electronic structure of the carbon nitride itself can be regulated, the number of surface active sites of the photocatalytic material can be increased, the charge transfer can be accelerated, and the efficiency of hydrogen production by ammonia decomposition can be improved.

[0022] In the present invention, iron is calculated as Fe2O3, nickel is calculated as NiO, and cobalt is calculated as Co3O4.

[0023] The inventors of the present invention have found in their research that the ratio of nitrogen to carbon in the carbon nitride-based photocatalytic materials in the prior art is difficult to control, and the carbon content in the carbon nitride is too high, generally 0.8-0.85:1, which is not conducive to improving the efficiency of the photocatalytic material in hydrogen production by decomposing ammonia. Preferably, in the photocatalytic material, the molar ratio of carbon to nitrogen is 0.7-0.8:1, and more preferably 0.74-0.76:1, based on the elements.

[0024] In the present invention, the molar ratio of carbon to nitrogen is measured by X-ray fluorescence spectrometry.

[0025] In the present invention, preferably, the mass ratio of nitrogen calculated as carbon nitride to the non-precious metal calculated as oxide is 100:2-8, and more preferably 100:3-6.

[0026] In the present invention, preferably, the mass ratio of nitrogen calculated as carbon nitride to the precious metal calculated as an element is 100:0.1-2, and more preferably 100:0.2-0.8.

[0027] In the present invention, preferably, the mass ratio of nitrogen calculated as carbon nitride to the phosphorus calculated as an element is 100:0.5-10, and more preferably 100:3-8.

[0028] In the above preferred case, it is beneficial to increase the number of surface active sites of the photocatalytic material and accelerate charge transfer, thereby improving the efficiency of photocatalytic ammonia decomposition to produce hydrogen.

[0029] In the present invention, preferably, the mass ratio of the noble metal to phosphorus is 0.05-0.5: 1, more preferably 0.05-0.18: 1, calculated as the element. The advantage of adopting this preferred embodiment is to optimize the ratio to control the light absorption performance and free carrier density, and improve the efficiency of hydrogen production by decomposing ammonia.

[0030] In the present invention, the content of each component in the photocatalytic material is obtained by X-ray fluorescence spectrum analysis during the preparation of the catalytic material.

[0031] In the present invention, the presence of a carbon nitride covalent skeleton in the photocatalytic material is indicated by an X-ray diffraction pattern test. Preferably, in the X-ray diffraction pattern of the photocatalytic material, typical carbon nitride diffraction peaks appear at 2θ of 13.6° and 27.2°, and there are no obvious diffraction peaks of phosphorus and precious metals, proving that the photocatalytic material has a carbon nitride covalent skeleton structure, and phosphorus and precious metals are present in the carbon nitride covalent skeleton in the form of doping.

[0032] In the present invention, phosphorus and noble metal exist in the carbon nitride covalent skeleton in the form of doping, which means that phosphorus replaces the carbon element in the carbon nitride skeleton, and the noble metal is located in the carbon nitride triazine ring cavity and coordinated with nitrogen.

[0033] In the present invention, the non-noble metal is loaded outside the carbon nitride covalent framework in the form of oxides, which means that the non-noble metal oxides are loaded on the carbon nitride framework in the form of nanoparticles or clusters.

[0034] In the present invention, the free carrier density of the photocatalytic material can be increased by combining phosphorus, noble metals and non-noble metal elements, thereby improving the efficiency of hydrogen production by decomposing ammonia. Preferably, the free carrier density of the photocatalytic material is (2-6)×10 22 cm -3 , and more preferably (3-5)×10 22 cm -3 The advantages of adopting this preferred embodiment are to optimize the carrier density, facilitate the separation and transmission of photogenerated charges, and improve the photocatalytic efficiency.

[0035] A second aspect of the present invention provides a method for preparing a photocatalytic material, wherein the method comprises the following steps:

[0036] (1) mixing a nitrogen-containing organic compound with a phosphorus source and a noble metal source, and then performing rotary evaporation drying, a first roasting and freeze drying, wherein the noble metal is selected from at least one of ruthenium, platinum and palladium;

[0037] (2) mixing the product obtained in step (1) with a non-precious metal source in the presence of a solvent, wherein the non-precious metal is at least one of iron, cobalt and nickel;

[0038] (3) Under a protective atmosphere, the product obtained in step (2) is subjected to a second calcination, wherein the second calcination comprises first keeping the temperature at 100-200° C. for 0.5-2 h, and then heating the temperature to 210-350° C. for 1-2 h.

[0039] The preparation method of the photocatalytic material provided by the present invention first prepares a carbon nitride precursor containing phosphorus and precious metals, so that the phosphorus and precious metals exist in the carbon nitride covalent skeleton in the form of doping, and then realizes co-doping of non-precious metals through in-situ synthesis, so that the non-precious metals exist outside the carbon nitride covalent skeleton in the form of oxides. The preparation method is simple and easy to control.

[0040] In the present invention, the nitrogen-containing organic matter refers to an organic matter containing both carbon and nitrogen, in particular, a nitrogen-containing small molecule organic matter that can be decomposed during the roasting process, which can provide a nitrogen source and a carbon source at the same time during the first roasting process. The present invention has a wide range of selection for the nitrogen-containing organic compound, and conventional substances in the art can be used. Preferably, in step (1), the nitrogen-containing organic compound is selected from at least one of melamine, dicyandiamide and urea, and is more preferably melamine.

[0041] In the present invention, the phosphorus source can be selected from a wide range of types, as long as it can provide phosphorus. Preferably, in step (1), the phosphorus source is an alkali metal phosphate and / or an alkali metal hypophosphite, more preferably sodium hypophosphite and / or potassium hypophosphite.

[0042] In the present invention, the selection range of the type of precious metal source is relatively wide, as long as it can provide non-precious metal elements. Preferably, in step (1), the precious metal source is a soluble salt of a precious metal, more preferably a soluble inorganic salt of a precious metal, and more preferably at least one selected from nitrates, sulfates and chlorides of precious metals.

[0043] In the present invention, preferably, in step (1), the conditions for the rotary evaporation drying include: a temperature of 40-80°C, more preferably 60-70°C.

[0044] In the present invention, the range of conditions for the first calcination is relatively wide. Preferably, in step (1), the temperature is 300-700°C, the time is 3-6h, and the heating rate is 2-10°C / min; further preferably, in step (1), the conditions for the first calcination include: temperature is 500-600°C, time is 4-5h, and heating rate is 2-5°C / min.

[0045] In the present invention, preferably, the first calcination is carried out under an inert atmosphere, and the gas flow rate of the inert atmosphere is 20-100 mL / min relative to 20 g of the nitrogen-containing organic compound in step (1).

[0046] In the present invention, the range of freeze-drying conditions is relatively wide. Preferably, in step (1), the freeze-drying conditions include: a temperature of -50°C to -20°C and a time of 20-48h. The inventors of the present invention have found in their research that drying at a low freezing temperature can allow phosphorus and precious metals to be in-situ doped into the carbon nitride skeleton. When the drying temperature is not within the above preferred range, a too high drying temperature may cause the precious metal particles to agglomerate, and a too low drying temperature may result in a high energy consumption of the process.

[0047] In the present invention, preferably, the method further comprises washing the roasted product obtained after the first roasting before freeze drying. In the present invention, the type of detergent for washing is not particularly limited, and detergents conventionally defined in the art are all applicable to the present invention, such as water and / or ethanol. In the present invention, the manner of washing is not particularly limited, for example, water and ethanol can be used for washing respectively. In the present invention, the number of washings is not particularly limited, as long as the sodium phosphate impurities generated by roasting can be removed, and preferably, the number of washings is such that the content of sodium phosphate impurities in the roasted product is <0.2% by weight.

[0048] In the present invention, the type of non-precious metal source can be selected in a wide range, as long as it can provide non-precious metal elements. Preferably, in step (2), the non-precious metal source is a soluble salt of a non-precious metal, preferably a soluble inorganic salt of a non-precious metal, and more preferably at least one selected from nitrates, sulfates and chlorides of non-precious metals.

[0049] In the present invention, there is no particular limitation on the order of mixing the components in step (2). The product obtained in step (1) can be first dispersed in a solvent and then the non-precious metal source can be added. Alternatively, the product obtained in step (1) and the non-precious metal source can be separately dissolved in a solvent and then mixed.

[0050] In the present invention, the range of solvents is relatively wide, as long as the dissolution of each component is achieved. Preferably, in step (2), the solvent is water. Preferably, no organic solvent is used in step (2), and the synthesis process is green and environmentally friendly, which is conducive to large-scale production.

[0051] In the present invention, the formation of graphite phase carbonized nitrogen structure is achieved by segmented calcination and regulating the reaction conditions of different calcination stages. Preferably, the second calcination includes first keeping warm at 150-200°C for 0.5-1.5h, and then heating to 250-350°C for 1.5-2h. The segmented calcination within the above range is conducive to promoting the exfoliation of the carbon nitride interlayer structure and forming a graphite phase structure; when one-stage calcination is adopted, it is not conducive to the formation of ultra-thin interlayer structure; when the temperature of the second calcination is not within the above preferred range, the temperature of the second calcination is too high, which may cause the interlayer structure to agglomerate, and the temperature of the second calcination is too low, which may make it difficult to form a graphite phase structure, which is not conducive to the improvement of photocatalytic efficiency.

[0052] In the present invention, preferably, in step (3), the conditions for the second calcination include: a heating rate of 2-10° C. / min.

[0053] In the present invention, the protective atmosphere refers to a gas that does not participate in the reaction and is used to avoid the introduction of oxygen during the roasting process. Preferably, the protective atmosphere is provided by at least one of nitrogen, argon and helium. The present invention has a wide range of selection for the flow rate of the protective atmosphere. Preferably, the gas flow rate of the protective atmosphere is 20-100 mL / min.

[0054] In the present invention, preferably, the mass ratio of the nitrogen-containing organic compound calculated as carbon nitride to the non-precious metal source calculated as oxide is 100:2-8, and more preferably 100:3-6.

[0055] In the present invention, preferably, the mass ratio of the nitrogen-containing organic compound calculated as carbon nitride to the precious metal source calculated as the element is 100:0.1-2, and more preferably 100:0.2-0.8.

[0056] In the present invention, preferably, the mass ratio of the nitrogen-containing organic compound calculated as carbon nitride to the phosphorus source calculated as an element is 100:0.5-10, and more preferably 100:3-8.

[0057] In the present invention, preferably, the mass ratio of the noble metal source to the phosphorus source is 0.05-0.5:1, and more preferably 0.05-0.18:1, calculated on an element basis.

[0058] The third aspect of the present invention provides a photocatalytic material prepared by the preparation method described in the second aspect.

[0059] A fourth aspect of the present invention provides an application of the photocatalytic material described in the first aspect or the third aspect in a photocatalytic ammonia decomposition hydrogen production reaction.

[0060] The fifth aspect of the present invention provides a method for producing hydrogen by photocatalytic decomposition of ammonia, wherein the method comprises: in the presence of a photocatalytic material and visible light, a decomposition reaction of the reaction raw material ammonia occurs, and the photocatalytic material is the photocatalytic material described in the first aspect or the third aspect.

[0061] In the present invention, preferably, the reaction raw material ammonia is provided by an ammonia aqueous solution, and the concentration of the ammonia aqueous solution is 0.01-0.1 mol / L.

[0062] In the present invention, preferably, the conditions of the decomposition reaction include: the reaction temperature is 0.5-40° C., and the amount of the photocatalytic material is 0.02-0.1 g relative to 0.01 mol of ammonia solution.

[0063] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, all the raw materials used are from commercially available products.

[0064] In the present invention, the content of each component in the photocatalytic material is obtained by X-ray fluorescence spectrum analysis during the preparation of the catalytic material.

[0065] Example 1

[0066] (1) Weigh 30g of melamine, 5g of sodium hypophosphite and 0.17g of ruthenium trichloride and disperse them in 50mL of water, mix them thoroughly and dry them by rotary evaporation at 60°C. The obtained product is roasted in an argon atmosphere at 550°C for 4h, with a heating rate of 5°C per minute and a gas flow rate of 40mL / min relative to 20g of melamine. After cooling, the obtained product is washed with water and ethanol three times respectively (the content of sodium phosphate impurities in the product is 0.1% by weight), dispersed in 50mL of water and freeze-dried at -40°C for 24h to obtain a phosphorus- and noble metal-doped carbon nitride precursor;

[0067] (2) adding 2.5 g of ferric nitrate nonahydrate to the phosphorus- and noble metal-doped carbon nitride precursor obtained in step (1), and grinding and mixing thoroughly;

[0068] (3) The product obtained in step (2) is subjected to a programmed temperature calcination treatment, wherein the temperature rise program is room temperature-150°C (1h)-300°C (1.5h), the heating rate is 5°C per minute, the calcination atmosphere is argon, the gas flow rate is 40mL / min, and the photocatalytic material is obtained after cooling.

[0069] Figure 1 This is the X-ray diffraction pattern of the photocatalytic material. It can be seen that typical carbon nitride characteristic peaks appear at 13.2° and 27.8°, proving that the carbon nitride structure is intact. Figure 2This is a high-resolution transmission electron micrograph of the photocatalytic material, which shows that the sample mainly exists in a two-dimensional graphene sheet structure. No obvious particles or clusters were observed in the sample, indicating that the precious metals ruthenium and phosphorus are highly dispersed and exist in the carbon nitride skeleton in a doped form.

[0070] Example 2

[0071] (1) Weigh 30g of melamine, 5g of sodium hypophosphite and 0.12g of ruthenium trichloride and disperse them in 50mL of water, mix them thoroughly and dry them by rotary evaporation at 60°C. The obtained product is roasted in an argon atmosphere at 520°C for 4h, with a heating rate of 5°C per minute and a gas flow rate of 40mL / min relative to 20g of melamine. After cooling, the obtained product is washed with water and ethanol three times respectively (the content of sodium phosphate impurities in the product is 0.1% by weight), dispersed in 50mL of water and freeze-dried at -40°C for 24h to obtain a phosphorus- and noble metal-doped carbon nitride precursor;

[0072] (2) adding 2.5 g of ferric nitrate nonahydrate to the phosphorus- and noble metal-doped carbon nitride precursor obtained in step (1), and grinding and mixing thoroughly;

[0073] (3) The product obtained in step (2) is subjected to a programmed temperature calcination treatment, wherein the temperature rise program is room temperature-150°C (1h)-300°C (1.5h), the heating rate is 5°C per minute, the calcination atmosphere is argon, the gas flow rate is 40mL / min, and the photocatalytic material is obtained after cooling.

[0074] Example 3

[0075] (1) Weigh 30g of melamine, 3g of sodium hypophosphite and 0.06g of ruthenium trichloride and disperse them in 50mL of water, mix them thoroughly and dry them by rotary evaporation at 60°C. The obtained product is roasted in an argon atmosphere at 550°C for 4h, with a heating rate of 5°C per minute and a gas flow rate of 60mL / min relative to 20g of melamine. After cooling, the obtained product is washed with water and ethanol three times respectively (the content of sodium phosphate impurities in the product is 0.08% by weight), dispersed in 50mL of water and freeze-dried at -40°C for 28h to obtain a phosphorus- and noble metal-doped carbon nitride precursor;

[0076] (2) adding 2.5 g of ferric nitrate nonahydrate to the phosphorus- and noble metal-doped carbon nitride precursor obtained in step (1), and grinding and mixing thoroughly;

[0077] (3) The product obtained in step (2) is subjected to a programmed temperature calcination treatment, wherein the temperature rise program is room temperature-150°C (1h)-300°C (1.5h), the heating rate is 5°C per minute, the calcination atmosphere is argon, the gas flow rate is 40mL / min, and the photocatalytic material is obtained after cooling.

[0078] Example 4

[0079] (1) Weigh 30g of melamine, 0.5g of sodium hypophosphite and 0.02g of ruthenium trichloride and disperse them in 50mL of water, mix them thoroughly and dry them by rotary evaporation at 60°C. The obtained product is roasted in an argon atmosphere at 550°C for 4h, with a heating rate of 5°C per minute and a gas flow rate of 40mL / min relative to 20g of melamine. After cooling, the obtained product is washed with water and ethanol three times respectively (the content of sodium phosphate impurities in the product is 0.05% by weight), dispersed in 50mL of water and freeze-dried at -40°C for 26h to obtain a phosphorus- and noble metal-doped carbon nitride precursor;

[0080] (2) adding 0.5 g of ferric nitrate nonahydrate to the phosphorus-containing carbon nitride precursor obtained in step (1), and grinding and mixing thoroughly;

[0081] (3) The product obtained in step (2) is subjected to a programmed temperature calcination treatment, wherein the temperature rise program is room temperature-200°C (0.5h)-300°C (1.5h), the heating rate is 5°C per minute, the calcination atmosphere is argon, the gas flow rate is 40mL / min, and the photocatalytic material is obtained after cooling.

[0082] Example 5

[0083] (1) Weigh 30g of melamine, 10g of sodium hypophosphite and 0.41g of ruthenium trichloride and disperse them in 60mL of water, mix them thoroughly and then dry them by rotary evaporation at 60°C. The obtained product is calcined at 550°C in an argon atmosphere for 4h, with a heating rate of 5°C per minute and a gas flow rate of 40mL / min relative to 20g of melamine. After cooling, the obtained product is washed with water and ethanol three times respectively (the content of sodium phosphate impurities in the product is 0.12% by weight), dispersed in 50mL of water and freeze-dried at -40°C for 20h to obtain a phosphorus- and noble metal-doped carbon nitride precursor;

[0084] (2) adding 2.0 g of ferric nitrate nonahydrate to the phosphorus- and noble metal-doped carbon nitride obtained in step (1), and grinding and mixing thoroughly;

[0085] (3) The product obtained in step (2) is subjected to a programmed temperature calcination treatment, wherein the temperature rise program is room temperature-150°C (1h)-300°C (1.5h), the heating rate is 5°C per minute, the calcination atmosphere is argon, the gas flow rate is 40mL / min, and the photocatalytic material is obtained after cooling.

[0086] Example 6

[0087] (1) Weigh 30g of melamine, 5g of sodium hypophosphite and 0.17g of ruthenium trichloride and disperse them in 50mL of water, mix them thoroughly and then dry them by rotary evaporation at 60°C. The obtained product is calcined at 650°C in an argon atmosphere for 3h, with a heating rate of 10°C per minute and a gas flow rate of 40mL / min relative to 20g of melamine. After cooling, the obtained product is washed with water and ethanol three times respectively (the content of sodium phosphate impurities in the product is 0.07% by weight), dispersed in 50mL of water and freeze-dried at -40°C for 22h to obtain a phosphorus- and noble metal-doped carbon nitride precursor;

[0088] (2) adding 2.5 g of ferric nitrate nonahydrate to the phosphorus- and noble metal-doped carbon nitride precursor obtained in step (1), and grinding and mixing thoroughly;

[0089] (3) The product obtained in step (2) is subjected to a programmed temperature calcination treatment, wherein the temperature rise program is room temperature-100°C (1h)-220°C (1.5h), the heating rate is 5°C per minute, the calcination atmosphere is argon, the gas flow rate is 40mL / min, and the photocatalytic material is obtained after cooling.

[0090] Example 7

[0091] (1) Weigh 30g of melamine, 5g of sodium hypophosphite and 0.17g of ruthenium trichloride and disperse them in 50mL of water, mix them thoroughly and then dry them by rotary evaporation at 60°C. The obtained product is calcined at 550°C in an argon atmosphere for 4h, with a heating rate of 5°C per minute and a gas flow rate of 40mL / min relative to 20g of melamine. After cooling, the obtained product is washed with water and ethanol three times respectively (the content of sodium phosphate impurities in the product is 0.06% by weight), dispersed in 50mL of water and freeze-dried at -40°C for 22h to obtain a phosphorus- and noble metal-doped carbon nitride precursor;

[0092] (2) adding 2.2 g of cobalt nitrate hexahydrate to the phosphorus- and noble metal-doped carbon nitride precursor prepared in step (1), and grinding and mixing the mixture thoroughly;

[0093] (3) The product obtained in step (2) is subjected to a programmed temperature calcination treatment, wherein the temperature rise program is room temperature-150°C (1h)-300°C (1.5h), the heating rate is 5°C per minute, the calcination atmosphere is argon, the gas flow rate is 40mL / min, and the photocatalytic material is obtained after cooling.

[0094] Example 8

[0095] (1) Weigh 30g of melamine, 5g of sodium hypophosphite and 0.17g of chloroplatinic acid and disperse them in 50mL of water, mix them thoroughly and dry them by rotary evaporation at 60°C. The obtained product is calcined at 550°C in an argon atmosphere for 4h, with a heating rate of 5°C per minute and a gas flow rate of 40mL / min relative to 20g of melamine. After cooling, the obtained product is washed with water and ethanol three times respectively (the content of sodium phosphate impurities in the product is 0.1% by weight), dispersed in 50mL of water and freeze-dried at -40°C for 24h to obtain a phosphorus- and noble metal-doped carbon nitride precursor;

[0096] (2) adding 1.9 g of nickel nitrate hexahydrate to the phosphorus- and noble metal-doped carbon nitride precursor obtained in step (1), and grinding and mixing thoroughly;

[0097] (3) The product obtained in step (2) is subjected to a programmed temperature calcination treatment, wherein the temperature rise program is room temperature-150°C (1h)-300°C (1.5h), the heating rate is 5°C per minute, the calcination atmosphere is argon, the gas flow rate is 40mL / min, and the photocatalytic material is obtained after cooling.

[0098] Comparative Example 1

[0099] (1) Weigh 30g of melamine and 5g of sodium hypophosphite and disperse them in 50mL of water, mix them thoroughly and then dry them by rotary evaporation at 60°C. The obtained product is calcined at 550°C in an argon atmosphere for 4h, with a heating rate of 5°C per minute and a gas flow rate of 40mL / min relative to 20g of melamine. After cooling, the obtained product is washed with water and ethanol three times respectively (the content of sodium phosphate impurities in the product is 0.1% by weight), dispersed in 50mL of water and freeze-dried at -40°C for 24h to obtain a phosphorus-doped carbon nitride precursor;

[0100] (2) adding 2.5 g of ferric nitrate nonahydrate to the phosphorus-doped carbon nitride precursor obtained in step (1), and grinding and mixing thoroughly;

[0101] (3) The product obtained in step (2) is subjected to a programmed temperature calcination treatment, wherein the temperature rise program is room temperature-150°C (1h)-300°C (1.5h), the heating rate is 5°C per minute, the calcination atmosphere is argon, the gas flow rate is 40mL / min, and the photocatalytic material is obtained after cooling.

[0102] Comparative Example 2

[0103] Weigh 30g of melamine, 5g of sodium hypophosphite and 0.17g of ruthenium trichloride and disperse them in 50mL of water, mix thoroughly and dry them by rotary evaporation at 60°C. The obtained product is roasted in an argon atmosphere at 550°C for 4h, with a heating rate of 5°C per minute and a gas flow rate of 40mL / min relative to 20g of melamine. After cooling, the obtained product is washed with water and ethanol three times respectively (the content of sodium phosphate impurities in the product is 0.1% by weight), dispersed in 50mL of water and freeze-dried at -40°C for 24h to obtain phosphorus- and precious metal-doped carbon nitride.

[0104] Comparative Example 3

[0105] (1) Weigh 30g of melamine and 5g of sodium hypophosphite and disperse them in 50mL of water, mix them thoroughly and then dry them by rotary evaporation at 60°C. The obtained product is calcined at 550°C in an argon atmosphere for 4h, with a heating rate of 5°C per minute and a gas flow rate of 40mL / min relative to 20g of melamine. After cooling, the obtained product is washed with water and ethanol three times respectively (the content of sodium phosphate impurities in the product is 0.1% by weight), dispersed in 50mL of water and freeze-dried at -40°C for 24h to obtain a phosphorus-doped carbon nitride precursor;

[0106] (2) adding 2.5 g of ferric nitrate nonahydrate and 0.17 g of ruthenium trichloride to the phosphorus-doped carbon nitride precursor obtained in step (1), and grinding and mixing thoroughly;

[0107] (3) The product obtained in step (2) is subjected to a programmed temperature calcination treatment, wherein the temperature rise program is room temperature-150°C (1h)-300°C (1.5h), the heating rate is 5°C per minute, the calcination atmosphere is argon, the gas flow rate is 40mL / min, and the photocatalytic material is obtained after cooling.

[0108] Comparative Example 4

[0109] Disperse 5g of sodium hypophosphite in 50mL of water, then add 30g of melamine to the system, mix well and dry by rotary evaporation at 60°C, then calcine the product at 550°C in an argon atmosphere for 4h, with a heating rate of 5°C per minute, and a gas flow rate of 40mL / min relative to 20g of melamine, to obtain phosphorus-doped carbon nitride; mix phosphorus-doped carbon nitride with 0.5g of ferric oxide and 0.11g of ruthenium dioxide, add 50mL of ethanol to disperse, mix well and dry by rotary evaporation at 60°C, then calcine the product at 550°C in an argon atmosphere for 4h, with a heating rate of 5°C per minute, and a gas flow rate of 40mL / min, to obtain a photocatalytic material.

[0110] Comparative Example 5

[0111] (1) Weigh 30 g of melamine, 5 g of sodium hypophosphite and 0.17 g of ruthenium trichloride and disperse them in 50 mL of water, mix thoroughly and dry them by rotary evaporation at 60° C. The obtained product is roasted at 550° C. in an argon atmosphere for 4 h, with a heating rate of 5° C. per minute and a gas flow rate of 40 mL / min relative to 20 g of melamine. After cooling, the obtained product is washed three times with water and ethanol respectively (the content of sodium phosphate impurities in the product is 0.15% by weight), dispersed in 50 mL of water and freeze-dried at -40° C. to obtain phosphorus- and precious metal-doped carbon nitride;

[0112] (2) adding 2.5 g of ferric nitrate nonahydrate to the phosphorus- and noble metal-doped carbon nitride obtained in step (1), and grinding and mixing thoroughly;

[0113] (3) The product obtained in step (2) is subjected to a programmed temperature calcination treatment, wherein the temperature rise program is room temperature to 300°C (4h), the temperature rise rate is 5°C per minute, the calcination atmosphere is argon, and the gas flow rate is 40mL / min. After cooling, the photocatalytic material is obtained.

[0114] The contents of the components in the above-mentioned photocatalytic material are shown in Table 1, and the property parameters are shown in Table 2.

[0115] Table 1

[0116]

[0117] Table 2

[0118]

[0119]

[0120] It can be seen from the above table that the photocatalytic material provided by the present invention has a good visible light absorption range and a large free carrier density, which is beneficial to improving the efficiency of photocatalytic ammonia decomposition to produce hydrogen.

[0121] Application of photocatalytic ammonia decomposition to produce hydrogen

[0122] The photocatalytic materials prepared in the above embodiments and comparative examples were used in the photocatalytic ammonia decomposition hydrogen production reaction under simulated sunlight, and the activity test was carried out using an online vacuum photocatalytic reaction device, and the light source was a 300W xenon lamp. The reaction conditions are: 0.1g of catalytic material, 100mL of 0.1mol / L ammonia solution, and a reaction temperature of 5°C. After the reaction started, sampling was performed every 1 hour to determine the average rate within 6 hours. The chromatographic analysis product was analyzed using a hydrogen flame ionization detector and a thermal conductivity cell detector, and the standard curve determined in advance was used for quantification. The reaction mainly generates two products, namely N2 and H2, and a small amount of O2 from the side reaction of water decomposition. The reaction results are shown in Table 3.

[0123] Table 3

[0124]

[0125]

[0126] It can be seen from the above table that the photocatalytic material provided by the present invention has good performance of hydrogen production by decomposing ammonia, and the hydrogen generation rate can reach 1307.4 μmol g -1 h -1 Compared with Example 1, in Comparative Example 3, both the noble metal ruthenium and the non-noble metal iron are doped outside the carbon nitride skeleton structure. When the photocatalytic material prepared in Comparative Example 3 is used for ammonia decomposition to produce hydrogen, the hydrogen generation rate is only 373.8 μmol g -1 h -1 Compared with Example 1, the second calcination in step (3) of Comparative Example 5 uses a single-stage calcination to prepare the photocatalytic material. There are more hydrogen bonds and interlayer stacking between carbon nitrides, resulting in too low free carrier density, serious charge recombination, and poor activity. The photocatalytic material prepared in Comparative Example 5 is used for hydrogen production by decomposing ammonia. The hydrogen generation rate is only 270.3 μmol g -1 h -1 .

[0127] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A photocatalytic material, characterized in that: The photocatalytic material includes nitrogen, carbon, phosphorus, non-precious metals and precious metals. The photocatalytic material has a carbon nitride covalent skeleton, phosphorus and precious metals are present in the carbon nitride covalent skeleton in the form of doping, and the non-precious metals are loaded outside the carbon nitride covalent skeleton in the form of oxides; the non-precious metal is selected from at least one of iron, cobalt and nickel, and the precious metal is selected from at least one of ruthenium, platinum and palladium.

2. The photocatalytic material according to claim 1, wherein In the photocatalytic material, the molar ratio of carbon to nitrogen, calculated as elements, is 0.7-0.8:1, preferably 0.74-0.76:

1.

3. The photocatalytic material according to claim 1 or 2, wherein: The mass ratio of nitrogen calculated as carbon nitride to the non-precious metal calculated as oxide is 100:2-8, preferably 100:3-6; Preferably, the mass ratio of nitrogen calculated as carbon nitride to the precious metal calculated as an element is 100:0.1-2, more preferably 100:0.2-0.8; Preferably, the mass ratio of nitrogen calculated as carbon nitride to the phosphorus calculated as an element is 100:0.5-10, more preferably 100:3-8; Preferably, calculated on an element basis, the mass ratio of the noble metal to phosphorus is 0.05-0.5:1, more preferably 0.05-0.18:

1.

4. The photocatalytic material according to any one of claims 1 to 3, wherein: In the X-ray diffraction spectrum of the photocatalytic material, typical carbon nitride diffraction peaks appear at 2θ of 13.6° and 27.2°; Preferably, the free carrier density of the photocatalytic material is (2-6)×10 22 cm -3 , and more preferably (3-5)×10 22 cm -3 .

5. A method for preparing a photocatalytic material, wherein: The method comprises the following steps: (1) mixing a nitrogen-containing organic compound with a phosphorus source and a noble metal source, and then performing rotary evaporation drying, a first roasting and freeze drying, wherein the noble metal is selected from at least one of ruthenium, platinum and palladium; (2) mixing the product obtained in step (1) with a non-precious metal source in the presence of a solvent, wherein the non-precious metal is selected from at least one of iron, cobalt and nickel; (3) Under a protective atmosphere, the product obtained in step (2) is subjected to a second calcination, wherein the second calcination comprises first keeping the temperature at 100-200° C. for 0.5-2 h, and then heating the temperature to 210-350° C. for 1-2 h.

6. The method according to claim 5, wherein: In step (1), the nitrogen-containing organic compound is selected from at least one of melamine, dicyandiamide and urea; Preferably, in step (1), the phosphorus source is an alkali metal phosphate and / or an alkali metal hypophosphite, preferably sodium hypophosphite and / or potassium hypophosphite; Preferably, in step (1), the noble metal source is a soluble salt of a noble metal, more preferably a soluble inorganic salt of a noble metal, and even more preferably at least one selected from nitrates, sulfates and chlorides of the noble metal; Preferably, in step (1), the conditions for rotary evaporation drying include: a temperature of 40-80°C, more preferably 60-70°C; Preferably, in step (1), the conditions of the first calcination include: temperature of 300-700°C, time of 3-6h, and heating rate of 2-10°C / min; Further preferably, in step (1), the conditions of the first calcination include: temperature of 500-600°C, time of 4-5h, and heating rate of 2-5°C / min; Preferably, the first calcination is carried out under an inert atmosphere, and the gas flow rate of the inert atmosphere is 20-100 mL / min relative to 20 g of the nitrogen-containing organic compound in step (1); Preferably, in step (1), the freeze-drying conditions include: a temperature of -50°C to -20°C and a time of 20-48 hours.

7. The method according to claim 5 or 6, wherein: In step (2), the non-precious metal source is a soluble salt of a non-precious metal, preferably a soluble inorganic salt of a non-precious metal, and further preferably at least one selected from nitrates, sulfates and chlorides of non-precious metals; Preferably, in step (2), the solvent is water.

8. The method according to any one of claims 5 to 7, wherein: In step (3), the second calcination includes first keeping the temperature at 150-200°C for 0.5-1.5h, then heating to 250-350°C and keeping the temperature for 1.5-2h; Preferably, in step (3), the conditions of the second calcination include: a heating rate of 2-10°C / min; Preferably, the protective atmosphere is provided by at least one of nitrogen, argon and helium.

9. The method according to any one of claims 5 to 8, wherein: The mass ratio of the nitrogen-containing organic compound calculated as carbon nitride to the non-precious metal source calculated as oxide is 100:2-8, preferably 100:3-6; Preferably, the mass ratio of the nitrogen-containing organic compound calculated as carbon nitride to the precious metal source calculated as the element is 100:0.1-2, and more preferably 100:0.2-0.8; Preferably, the mass ratio of the nitrogen-containing organic compound calculated as carbon nitride to the phosphorus source calculated as an element is 100:0.5-10, more preferably 100:3-8; Preferably, calculated on an element basis, the mass ratio of the noble metal source to the phosphorus source is 0.05-0.5:1, more preferably 0.05-0.18:

1.

10. The photocatalytic material obtained by the preparation method according to any one of claims 5 to 9.

11. Use of the photocatalytic material according to any one of claims 1 to 4 and 10 in a photocatalytic ammonia decomposition reaction to produce hydrogen.

12. A method for producing hydrogen by photocatalytic decomposition of ammonia, wherein: The method comprises: in the presence of a photocatalytic material and visible light, ammonia, a reaction raw material, undergoes a decomposition reaction, wherein the photocatalytic material is the photocatalytic material according to any one of claims 1 to 4 and 10; Preferably, the reaction raw material ammonia is provided by an ammonia solution, and the concentration of the ammonia solution is 0.01-0.1 mol / L; Preferably, the conditions of the decomposition reaction include: a reaction temperature of 0.5-40° C., and an amount of the photocatalytic material of 0.02-0.1 g relative to 0.01 mol of an aqueous ammonia solution.

Citation Information

Patent Citations

  • Pholocatalyst for metallic oxide doping and preparation method thereof

    CN106492870A

  • Preparation method for metal single atom / phosphor doping carbon nitride photocatalyst

    CN108906105A

  • Preparation method of nanogold co-doping iron oxide compound catalytic electrode, catalytic electrode and water electrolysis equipment

    CN110438526A

  • Preparation method, product and application of low-temperature phosphorus-doped carbon nitride loaded high-dispersion palladium hydrogen evolution catalyst

    CN111774083A

  • Preparation method of palladium / phosphorus doped carbon nitride composite material as well as product and application of palladium / phosphorus doped carbon nitride composite material

    CN112295587A